PELAKSANAAN KMA RI NO. 298 TAHUN 2003 PASAL 2 TENTANG PENGAWASAN DAN PENCATATAN PERNIKAHAN PADA MUSIM PANDEMI COVID 19: Studi Kasus KUA kecamatan Jombang - Abd. Basit Misbachul Fitri (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2021)
Supervision and registration of marriage is something that is urgent for the sake of being recognized and legislated by the state because it is a very important event. The Indonesian nation has been hit by covid 19 since March 2020 until now it has not ended, this virus is a pandemic category so it is not certain when it will end, spreading throughout the world. The research used the interview method conducted by researchers to Jombang District KUA officers in December 2020 regarding the activities of the KUA Jombang sub-district in the covid 19 pandemic season. The results of this study were the Jombang District Religious Affairs Office still carrying out the task of registering marriage but by using a breakthrough in online registration. according to the specified address, in the supervision of the implementation of the marriage contract council accompanied by Imamuddin in their respective village areas virtually by using video calls and active marriage registration without any rejection of marriage registration. The KUA of Jombang sub-district has also decided to lock down, namely closing the office and imposing WFH (work from home), where work is done from home. This was done in order to anticipate and reduce the spread of the Covid 19 virus because its impact is very dangerous for the safety of life. As the data collected by the Covid 19 cluster in Jombang sub-district in March-June 2020, Jombang sub-district experienced a red zone in the spread of covid 19, so a breakthrough was needed in the form of policies that provided errors and safety for Jombang sub-district residents in terms of administrative services for recording and implementing marriage contracts. This is done based on maqashid sharia, namely hifd an-Nafs, which is to protect life / soul and also in the form of syad ad-dzariah to prevent mafsadah / damage. The existence of the KUA policy of Jombang sub-district without prejudice to the implementation of the Decree of the Minister of Religion number 298 of 2003 concerning supervision and supervision and registration of marriages.